Current Practices and Gaps in Management of Dyslipidemia in Type 2 Diabetes Mellitus (T2DM) in Accordance with American Diabetes Association (ADA) Guidelines: A Subset Analysis from a Real-World, Cross-Sectional Observational Study (LEADD Study) - Das, Ashok Kumar (Diabetes Metab Syndr Obes, 2021)
BACKGROUND: Diabetic dyslipidemia is a risk factor for coronary artery disease (CAD) in patients with type 2 diabetes mellitus (T2DM). American Diabetes Association (ADA) provides internationally accepted guidelines to manage dyslipidemia in T2DM. OBJECTIVE: To assess if ADA guidelines are followed for managing dyslipidemia in patients with T2DM in India. METHODS: This was a subset analysis of a prospective, cross sectional, observational study (LEADD Study) conducted at 199 sites across India to evaluate dyslipidemia management practices in T2DM patients (N=4002), in a real-world setting. The data was stratified based on age and atherosclerotic cardiovascular disease (ASCVD) and ASCVD risk factors to record the percentages of T2DM patients achieving LDL-C target and treated optimally with the Guideline directed intensity of statin. Analysis was conducted using descriptive statistics. RESULTS: As per ADA 2018 targets: LDL-C levels (<100mg/dL) were seen in 30.6% of participants. High intensity statins were prescribed to 13.4% of the participants with LDL levels ≥100 mg/dL. ASCVD risk assessment details were available for 89.2% of participants. Data was not available for smoking and albuminuria. In participants <40 years of age, 80% and 64.2% with ASCVD and ASCVD risk factors, respectively, did not achieve target LDL-C levels. In this age group, 15.6% and 83.3% of participants with ASCVD risk factors and ASCVD group, respectively, were not receiving statins in the recommended dose. In participants ≥40 years of age, 88.0% and 91.5% with ASCVD and ASCVD risk factors, respectively, did not have LDL-C levels as per ADA 2018 targets. In this age group, 87.2% and 77.9% of participants with ASCVD risk factors and ASCVD, respectively, were not receiving statins in the recommended dose. CONCLUSION: The sub-analysis of LEADD study shows sub-optimal adherence to ADA 2018 guidelines for management of diabetic dyslipidemia.